Dynamic energy modelling for analysis of the thermal and hygroscopic environment in a mechanically ventilated duck house. (December 2020) - Lee, Sang-Yeon; Lee, In-Bok; Kim, Rack-Woo; Yeo, Uk-Hyeon; Kim, Jun-Gyu; Kwon, Kyeong-Seok
Abstract : Thermal and hygroscopic environments inside a duck house are two of the most important factors directly related to their productivity and energy costs. However, few quantitative analyses of these environments have been performed. The objective of this study was to develop a dynamic energy model for the combined and real-time quantitative analysis of thermal and hygroscopic environments inside a mechanically ventilated duck house. To identify seasonal problems and develop the energy model, the internal and external environments of the duck house were first monitored via field experiments. Additionally, chamber experiments were conducted in a temperature- and humidity-controlled chamber to calculate the amount of evaporation from duck-house litter for incorporation of these data into the energy model. According to the environmental data measured in the field experiments and the results of the chamber experiments, the dynamic energy model of the duck house was developed using building energy simulation (BES). The BES model was validated by comparison of the BES-computed and field-measured data of the air temperature and relative humidity. The results showed errors of 1.71% and 4.33% for the air temperature and relative humidity, respectively. Finally, the validated BES model of the duck house was used to analyse the seasonal periodic and maximum energy loads. Furthermore, the high-temperature stress of the ducks in summer was also estimated for different space allowances . Highlights: Chamber experiments to measure the amount of evaporation from duck-house litter. BES model for analysing the thermal and hygroscopic environments in the duck house. Analysis of the seasonal periodic and maximum energy loads of the duck house.